Exercise-induced asthma: Incidence and pathology among elite athletes - Rundell, K. W. (5th IOC World Congress on Sport Sciences with the Annual Conference of Science and Medicine in Sport 1999, 1999)
A higher incidence of EIA has been estimated for cold-weather athletes than for warm-weather athletes, although limited data is available among elite athletes. The prevalence of asthma among elite athletes has been reported to be greater than that in the general population (3-7%). A 20% estimate of EIA among the 1996 U.S. Summer Olympians was recently reported. Estimates for winter sport athletes have been in the 30% range, depending on the particular sport surveyed. We have identified a 23% incidence of EIA (>10% post-exercise decrement in FEV1) among 1998 U.S. Winter Olympians. Additionally, we found 33% of the U.S. Junior Slalom Paddling Team positive for EIA, but only ~4% of the U.S. flat-water team was EIA positive. The prevalence of EIA in elite athletes appears to be sport/environment specific. EIA is high in sports where high ventilation rates in cold climatic conditions prevail or in sports that take place in environments high in chemical irritants (e.g. indoor rinks, waxing rooms, boat repair rooms). The excessive use of beta-2 agonists for relief of EIA symptoms during sport has become a controversial issue. Implications that healthy athletes use anti-asthmatic drugs to try to improve performance have been made, albeit the proposed ergogenic boost in normal athletes is questionable. This has recently led the IOC Medical Commission to require a diagnosis of asthma (by a team or respiratory physician) for beta-2 agonist use. A diagnosis of exercise-induced bronchospasm (EIB) for beta-2 agonist use is no longer acceptable. The long-range implications of this ruling may necessitate a documented, detailed evaluation including appropriate pulmonary function tests for confirmation of asthma. Recent evidence suggests that current clinical protocols for EIA screening used for the general population ma y not be appropriate for elite athletes. Identification of EIA in this group can be confounded by conditions of the exercise challenge. We found that 78% of sport/environment-specific exercise challenged EIA positive cold weather athletes exhibited normal spirometry with a standard clinical screening procedure. For these athletes (contrary to literature on the non-athletic population) duration of the challenge (1.5 min - > 1 h) did not affect the appearance of EIA. Additionally, reported symptoms from PFT+ athletes (57%) was not different from PFTnormal athletes (48%). This implies that: 1) If the exercise challenge during pulmonary function testing is not sport/environment specific, a large number of false negatives will be reported. 2) If EIA diagnosis is made only on reported symptoms, false negative and false positive diagnoses will be made. Recent data suggests that the pathophysiology of the asthmatic athlete may be different than for the non-athletic asthmatic. Unlike the frank asthmatic, a large percentage of asthmatic elite athletes present small airway disease, which may be difficult to observe using standard spirometry. The lower limit reference range (mean maximal exercise-induced change in pulmonary functions minus 2SDs) from asymptomatic PFTnormal elite athletes suggests that the clinically recommended cut-off criteria for the non-athletic population (e.g. 10-15% in FEV1) may not be appropriate for elite athletes. We (and others) have suggested that a 6-7% post-exercise decrement in FEV1 is indicative of probable EIA. In summary, the asthmatic athlete presents unique problems for simple diagnosis by the physician, and the lack of appropriate medication removes this population from an even playing field with non-asthmatic athletes.